Oor paaie, sirkels en waarhede: 'n Bydrae met betrekking tot die huidige hermeneutiese gesprek - H J M van Deventer (Acta Theologica)
It is strived for in this article to make a contribution to the hermeneutical debate in South African biblical scholarship. The impetus for this article is the recent articles by Le Roux (1996) and Prinsloo (1996) relating to this matter. In this article the common roots of both the so-called historical approach(es) and tex-immanent approach(es) to biblical interpretation is traced back to Descartes. The movement in hermeneutics, introduced by Gadamer away from the Cartesian model, is also discussed. The arguments of Le Roux and Prinsloo are then viewed against this background, after which a suggestion is made regarding a way ahead.